PENGENDALI KECEPATAN MOTOR INDUKSI 3 FASA DENGAN INVERTER MODULASI LEBAR PULSA SERAGAM BERBASIS FPGA ACEX1K - Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2007)
The major disadvantage of pulse width modulation generating by microcontroller is that  the process completed in a longer period and slower system response then FPGA based system, while if based on DSP is its insufficiency in the case of flexibility and reliability. Speed demand will operate for and performance the reliable controller pushes for the implementation of evocation of PWM signal at FPGA. This research aim to design and to implement a device with uniform pulse width modulation based on FPGA Altera ACEX1K as drive inverter to control the rotational speed of a three phase induction motor. Design stage of implementing a UPWM signal generating system started from design entry, compiling, simulation and verification, and hardware configuration at FPGA Altera acex1k50tc144-3 development system with  MAX+Plus II 10.2 Baseline software. At this research, three phase inverter circuit designed using MOSFET SK727 with DC input voltage 310 V. Inverter output then loaded with a three phase induction motor Y2 712-4, 370W/380V, 50Hz model. Result of this research indicate that the generating of UPWM signal design can be implemented in the form of hardwared logic at FPGA Altera acex1k50tc144-3 development system, and applicable to drive inverter as rotational speed controller of a three phase induction motor. Speed regulating function of this system was implemented by modulation index and frequency setting. At this research, system have been tested at setting frequency 10-50 Hz with the variation of modulation index, and yield a range of range  458-1468 rpm using Three phase Motor mentioned above.